Hispanic products in Dalmatia and the Croatian part of Roman Pannonia - Borzić, Igor; Ožanić Roguljić, Ivana (Rei Cretariae Romanae Fautorum Acta, 2022)
In this paper we present the state of knowledge of Hispanic products in the wider area of the eastern Adriatic Sea (Dalmatia and Histria) and in the Croatian part of Roman Pannonia. In the 1st century CE and during the late Empire, the rhythm of Hispanic imports is characterized mostly by fish products. In the 2nd and 3rd century olive oil prevails in the study area, which is identical to the surrounding areas like Italy, Noricum and the remaining part of Pannonia. The number of more than 40 sites with Hispanic material in the study area is significant and very representative, but there is no doubt that it must be regarded as minimal. Some sites presented here are strong military and civilian centres, but most of them are underwater sites on previously established routes along the eastern Adriatic coast to the transit ports at the north that supplied the Central European mainland.